2011
DOI: 10.7763/ijtef.2011.v2.140
|View full text |Cite
|
Sign up to set email alerts
|

Applying Risk and Resilience Framework in Examining Youth’s Sustainability in Coping with Life’s Challenges

Abstract: This paper presents a study of youth's sustainability in coping with their life challenges from the risk and resilience conceptual framework. Specifically, the study examined the negative life events experienced by female and male respondents and how they cope with their challenges. A total of 428 youths (between 16-25 years old) participated in this study. Results showed that there seemed to be differences in the types of negative life events experienced by both female and male respondents. Female respondents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 18 publications
(19 reference statements)
0
4
0
1
Order By: Relevance
“…Variables with a p-value <0. 25 were selected for multivariable analysis to obtain the preliminary main effect model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Variables with a p-value <0. 25 were selected for multivariable analysis to obtain the preliminary main effect model.…”
Section: Discussionmentioning
confidence: 99%
“…Studies that examine the relationship between resilience and their associated factors among medical interns are still scarce, especially in Malaysia 25,26 . Accordingly, gaps to be investigated in this research relate to the lack of quantitative description of resilience as a product of other variables.…”
Section: Introductionmentioning
confidence: 99%
“…They are also more motivated and have higher self-confidence both academically and socially (Chan, 2000). In addition, a study in Malaysia by Lee (2011) revealed that people who have low levels of resilience will fail to cope with stressful situations. The implication is that highly resilient youths will (Earvolino-Ramirez, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Remaja yang memiliki resiliensi rendah cenderung akan menjadi individu yang lemah dan tidak berdaya (Purnomo, 2014) serta kesulitan dalam menghadapi situasi sulit atau situasi yang penuh tekanan karena tidak terbiasa untuk beradaptasi dengan tantangan (Lee, 2011). Begitu pun dengan yang memiliki resiliensi sedang cenderung tidak stabil dalam bersikap karena pengaturan emosi yang belum baik dan terkadang tidak semua permasalahan dapat mereka temukan akar permasalahan dan solusinya (Nisa & Muis, 2016).…”
Section: Pendahuluanunclassified